2019
DOI: 10.1136/bcr-2019-229554
|View full text |Cite
|
Sign up to set email alerts
|

Alport syndrome with bilateral simultaneous anterior and posterior lenticonus with severe temporal macular thinning

Abstract: Alport syndrome (AS) is a hereditary disease with various modes of inheritance, X-linked being the the most common. Anterior lenticonus is the characteristic abnormality along with perimacular and peripheral fleck retinopathy. Our two cases of AS had simultaneous anterior and posterior lenticonus with severe temporal macular thinning on optical coherence tomography with no specific renal symptomatology and were diagnosed as AS without any invasive renal biopsy. First patient was a 19-year-old man who presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Fukukita et al [ 32 ] investigated retinal changes in 26 AS patients living in Japan and discovered the same symptoms with the exclusion of retinal thinning and cataracts. Finally, several other studies by Gupta et al [ 37 ] who studied 2 AS patients in India and Wong et al who examined 1 AS patient in Australia [ 48 ] corroborated the lenticonus and retinopathies' presence. In total, these six studies showed 95 AS patients from six different countries with similar symptoms.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Fukukita et al [ 32 ] investigated retinal changes in 26 AS patients living in Japan and discovered the same symptoms with the exclusion of retinal thinning and cataracts. Finally, several other studies by Gupta et al [ 37 ] who studied 2 AS patients in India and Wong et al who examined 1 AS patient in Australia [ 48 ] corroborated the lenticonus and retinopathies' presence. In total, these six studies showed 95 AS patients from six different countries with similar symptoms.…”
Section: Resultsmentioning
confidence: 70%
“…AS ocular effects have yet to be proven to be alleviated by surgical approaches, such as vitrectomies, cataract surgeries, and IM peeling [ 29 , 32 , 35 , 37 , 38 , 47 ]. These techniques have been used to help target ocular findings and complications in non-AS patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temporal macular thinning on OCT has been highlighted as the commonest ocular finding in X-linked and recessive AS, with an incidence ranging from 75-90% in males and 55-75% in females. 6 Kandon et al reported a cohort of 32 patients with temporal macular thinning, which occurs frequently in male patients with XLAS; this specific sign helps not only for diagnosis but also for prognostication of XLAS. 5 Savige and colleagues had similar findings in their observation of 10 patients with Alport syndrome.…”
Section: Discussionmentioning
confidence: 99%